2020
DOI: 10.1111/cas.14452
|View full text |Cite
|
Sign up to set email alerts
|

High expression of PSF1 promotes drug resistance and cell cycle transit in leukemia cells

Abstract: Escape of cancer cells from chemotherapy is a problem in the management of cancer patients. Research on chemotherapy resistance has mainly focused on the heterogeneity of cancer cells, multiple gene mutations, and quiescence of malignant cancer cells. However, some studies have indicated that interactions between cancer cells and vascular cells promote resistance to chemotherapy. Here, we established mouse leukemia models using the cell lines THP‐1 or MEG‐1. These were derived from acute and chronic myeloid le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…GINS1 was required for cell proliferation in lung and colon carcinoma, and the inhibition of GINS1 suppressed the cell proliferation [ 64 , 65 ]. In cell cycle regulation, GINS1-knockdown caused cell cycle arrest at the quiescent G0/G1 phase in acute myelocytic leukemia and chronic myelocytic leukemia cells [ 23 ]. During the DNA replication, the GINS complex was recruited to form a complex, CDC45-MCM-GINS (CMG), triggering the elongation of replication [ 21 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GINS1 was required for cell proliferation in lung and colon carcinoma, and the inhibition of GINS1 suppressed the cell proliferation [ 64 , 65 ]. In cell cycle regulation, GINS1-knockdown caused cell cycle arrest at the quiescent G0/G1 phase in acute myelocytic leukemia and chronic myelocytic leukemia cells [ 23 ]. During the DNA replication, the GINS complex was recruited to form a complex, CDC45-MCM-GINS (CMG), triggering the elongation of replication [ 21 , 66 ].…”
Section: Discussionmentioning
confidence: 99%
“…The N-terminal domain forms an arch shape, and the C-terminal domain is on top of the arch [ 22 ]. In recent studies, GINS1 was reported to involve various processes of tumor genesis and development [ 23 , 24 ]. It has been demonstrated that GINS1 was highly expressed in various cancers, including intrahepatic cholangiocarcinoma, breast carcinoma, lung cancer, and colorectal cancer [ 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…The involvement of GINS subunits in malignancies has been reported in recent studies. For example, high expression of GINS1 promotes drug resistance in leukemia cells (Hsieh et al 2020) and help predicts clinical outcomes of colorectal cancer patients (Bu et al 2020b). On the other hand, high GINS4 results in tumorigenesis of human bladder cancer, colorectal cancer, and hepatocellular carcinoma (Yamane et al 2016;Rong et al 2020;Zhang et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These findings may reflect the mechanism of leukemia cells escaping from chemotherapy and suggest that Psf1 may be a therapeutic target to enhance the effect of chemotherapy. [34]…”
Section: The Prospect Of Psf1 In Tumor Researchmentioning
confidence: 99%